The Execution of the experts' plan. - Allied Powers (1919- ) Agent General for Reparation Payments; Allied Powers (1919- ) Office for Reparation Payments; Allied Powers (1919- ) Reparation Commission (Berlin Office for Reparation Payments, 1925)
Annual
v.1. Reports of the agent general for reparation payments. v.2. Reports of the commissioners and trustees.
According to article 4 of the Hague agreements of January 20, 1930, the functions of the Reparation commission, of the Office of reparation payments and of the organisations in Berlin connected with them, the maintennce of which was necessitated by the new plan, were transferred on May 17, 1930 to the Bank for international settlements.
In 2 v. each year, 1926/27-1928/30.
Keywords: World War, 1914-1918 -- Reparations -- Periodicals; Germany -- Economic conditions -- 1918-1945 -- Periodicals